Physical-Chemical and Nutritional Characterization of Somali Laxoox Flatbread and Comparison with Yemeni Lahoh Flatbread - Antonella Pasqualone; Francesca Vurro; Erin Wolgamuth; Salwa Yusuf; Giacomo Squeo; Davide De Angelis; Carmine Summo (Foods, 2023)
The physical–chemical and nutritional characteristics of Somali laxoox and Yemeni lahoh flatbreads have not been studied to date, nor have their possible similarities been investigated. Fieldwork was carried out in Somaliland (northwest Somalia), at nine different households, to collect Somali and Yemeni flatbreads. The nutritional characteristics (12.47–15.94 g/100 g proteins, 2.47–4.11 g/100 g lipids) and the total phenolic compounds (5.02–7.11 mg gallic acid equivalents/g on dry matter) were influenced by the natural variability of manual food preparation, as well as variability in the recipes used. All the breads had a porous structure. Cell density varied from 22.4 to 57.4 cells/cm2 in the Somali flatbreads, reaching 145 cells/cm2 in the Yemeni flatbreads. Higher amounts of refined flour increased the pale color of the breads. The principal component analysis highlighted differences between Yemeni and Somali flatbreads, pointing out a certain variability within the latter, with two samples forming a separate subgroup.